2015
DOI: 10.1186/s11671-015-1004-2
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of graphene using deep eutectic solvents

Abstract: Deep eutectic solvents (DESs) have received attention in various applications because of their distinctive properties. In this work, DESs were used as functionalizing agents for graphene due to their potential to introduce new functional groups and cause other surface modifications. Eighteen different types of ammonium- and phosphonium-salt-based DESs were prepared and characterized by FTIR. The graphene was characterized by FTIR, STA, Raman spectroscopy, XRD, SEM, and TEM. Additional experiments were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(87 citation statements)
references
References 81 publications
(83 reference statements)
9
67
0
Order By: Relevance
“…The Raman spectra of the investigated samples are given in Figure 3. The Raman spectra of the two samples are consistent with the one defined in the literature for graphene and graphite [54][55][56]. The assignment is made according to data given in [56].…”
Section: Raman Spectra Of Working Electrodessupporting
confidence: 73%
See 1 more Smart Citation
“…The Raman spectra of the investigated samples are given in Figure 3. The Raman spectra of the two samples are consistent with the one defined in the literature for graphene and graphite [54][55][56]. The assignment is made according to data given in [56].…”
Section: Raman Spectra Of Working Electrodessupporting
confidence: 73%
“…It was confirmed that this shift was not due to pure non calibration of the instrument. As indicated by Ferrari [55], a pronounced shift is particularly expected for the 2D band with an increasing number of the graphene layers. Thus, it can be concluded that these materials are different if the ratio between the integrated intensities of the D and G bands I D /I G for the two materials is calculated.…”
Section: Raman Spectra Of Working Electrodesmentioning
confidence: 75%
“…In addition, DES presented vibrational bands at 2938 cm −1 and 2875 cm −1 referring to C−H stretching, 1478 cm −1 to the CH 2 bending of an alkyl group, and 1084 cm −1 , 1036 cm −1 , and 882 cm −1 to functional groups, namely C−O stretching, C−C−O asymmetric stretching, and C−C−O symmetric stretching. 41 These results indicated the successful synthesis of ChCl:ethylene glycol DES.…”
Section: Characterization Of Chcl:ethylene Glycol Desmentioning
confidence: 82%
“…The use of traditional functionalization agents can cause side effects to the CNT surface and this will lower its performance. Therefore, the need for new environmentally friendly functionalization agent is crucial …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the need for new environmentally friendly functionalization agent is crucial. 21,22 Deep eutectic solvents (DESs) are a type of the ionic liquid analogy. The DESs are used as the ionic liquid (ILs) replacement as they are cheaper and environmentally friendly.…”
mentioning
confidence: 99%